2017
DOI: 10.1063/1.4981230
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear dynamics of turbulence driven magnetic islands. II. Numerical simulations

Abstract: The nonlinear dynamics of a turbulence driven magnetic island (TDMI) is investigated numerically in a reduced magnetohydrodynamic fluid model. The significance of identifying a characteristic signature of a TDMI for its experimental observation is discussed. The principal focus of our simulations is on the nature of the pressure profile flattening inside a TDMI, and we show that, in agreement with analytical predictions, a partial flattening occurs when the island size exceeds a critical value that is a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…25 Finally, we have proposed an explicit link between the level of the interchange source, the island size, and the pressure flattening inside the island. These analytical predictions were tested in Part II, 32 and we found a fairly good agreement with the numerical results.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…25 Finally, we have proposed an explicit link between the level of the interchange source, the island size, and the pressure flattening inside the island. These analytical predictions were tested in Part II, 32 and we found a fairly good agreement with the numerical results.…”
Section: Discussionsupporting
confidence: 65%
“…32 Thus, we will adopt the hypothesis that intermediate scales are almost adiabatic. (iii) From the mode number larger than m th: , it is found that there is a fast transition towards an equipartition between magnetic and pressure energies.…”
Section: Transport Properties Of Tdmis In the Nonlinear Phasementioning
confidence: 99%
“…Note that the separatrix of the magnetic island in the 2D T e profile can be roughly estimated by the temporal behavior of the electron temperature. A full 2D measured electron temperature profile and a proper modeling with a synthetic diagnostics are needed to estimate the magnetic island full width accurately [40,41], especially when the localized (not uniform) and dynamic turbulence exists around the magnetic island which can affect the perpendicular electron heat transport characteristics [42].…”
Section: The T E Profile With the Magnetic Islandmentioning
confidence: 99%
“…The former two instabilities were already described in the former 3-field code version 44 . The equations therein correspond to our equations (18), (19) and (22) with the remaining three fields n, p i and u assumed constant and without neoclassical terms. The ITG mode is new to our model, therefore we need to verify its presence.…”
Section: B Linear Analysis: Evidence Of Itg Modementioning
confidence: 99%
“…The interaction between turbulence and MHD phenomena in fusion device plasmas has received growing attention in the last decade, both in experimental 1-10 and theoretical context [11][12][13][14][15][16][17][18][19][20][21][22][23] . Basically, core MHD activity is dominated by sawteeth and neoclassical tearing modes (NTMs).…”
Section: Introductionmentioning
confidence: 99%